Risk Factors for Intrapartum Cesarean Section Delivery in Low-risk Multiparous Women Following at Least a Prior Vaginal Birth (Robson Classification 3 and 4) - Gul Nihal Buyuk; Hatice Kansu-Celik; Zeynep Asli Oskovi Kaplan; Burcu Kisa; Sule Ozel; Yaprak Engin-Ustun (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective The aim of the present study was to evaluate the risk factors for cesarean section (C-section) in low-risk multiparous women with a history of vaginal birth. Methods The present retrospective study included low-risk multiparous women with a history of vaginal birth who gave birth at between 37 and 42 gestational weeks. The subjects were divided into 2 groups according to the mode of delivery, as C-section Group and vaginal delivery Group. Risk factors for C-section such as demographic characteristics, ultrasonographic measurements, smoking, weight gain during pregnancy (WGDP), interval time between prior birth, history of macrosomic birth, and cervical dilatation at the admission to the hospital were obtained fromthe charts of the patients. Obstetric and neonatal outcomes were compared between groups. Results The most common C-section indications were fetal distress and macrosomia (33.9% [n=77 and 20.7% [n=47] respectively). A bivariate correlation analysis demonstrated that mothers aged>30 years old (odds ratio [OR]: 2.09; 95% confidence interval [CI]: 1.30-3.34; p=0.002), parity >1 (OR: 1.81; 95%CI: 1.18-2.71; p=0.006), fetal abdominal circumference (FAC) measurement>360mm (OR: 34.20; 95%CI: 8.04 -145.56; p<0.001)) and<345mm (OR: 3.06; 95%CI: 1.88-5; p<0.001), presence of large for gestational age (LGA) fetus (OR: 5.09; 95%CI: 1.35-19.21; p=0.016), premature rupture of membranes (PROM) (OR: 1.52; 95%CI: 1-2.33; p=0.041), and cervical dilatation<5cm at admission (OR: 2.12; 95%CI: 1.34-3.34; p=0.001) were associated with the group requiring a C-section. Conclusion This is the first study evaluating the risk factors for C-section in low-risk multiparous women with a history of vaginal birth according to the Robson classification 3 and 4. Fetal distress and suspected fetal macrosomia constituted most of the Csection indications.